Characteristics of Fault Detection System for Smart Grid Distribution Network - Gudzius, S.; Markevicius, L. A.; Morkvenas, A. (Elektronika ir Elektrotechnika, 2011)
The smart grid is the vision of the electric power network which integrates the electrotechnical, communication and informatics technologies. This integration allows developing new fault location technologies which are based on methods of fast transients analysis. The usage of these methods allows to locate the fault faster and more reliably or to prevent possible faults. The topic explains the structure of the fault location system for the smart electric power distribution network, discusses the challenges of smart grid fault location system and describes the method for one phase to ground fault location which is based on fast transient analysis. Ill. 2, bibl. 13 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.461